Mätning i nätstationer - nyttor och problem - Lindeberg, Annelie (My University, 2009)
The purpose of this study has been to investigate advantages and problems with distribution system metering in substations. This report is a study in cooperation with Göteborg Energi. The analyses in this report are made for GENAB, a subsidiary company of Göteborg Energi. To analyse advantages and problems in advance is interesting information for GENAB. The result of the report could be based upon whether installation of metering in distribution substations will be implemented and in that case which kind of measurement that is relevant. The most relevant and strategic place to implement measurement is at the distribution substations on the secondary side (400V), this is due to the placement of the current transformers. The measurements in this study involve current, voltage, power, power factor, temperature, energy and power quality. Measuring instruments that are relevant to implement are intended to measure current, voltage, power, power factor, energy and, possibly, power quality in the same measuring unit. It is desirable to have a measuring instrument that measures both energy and power quality but since it is most often a cost question, it can be established that energy meters have a lower cost. Metering in distribution substations gives a better illustration of the power network. This results in many advantages for GENAB. Approximately 30 advantages are identified in this report. The advantages and problems are rated on the basis of the different areas of activity at GENAB. The problems in this report are of general nature and they are not attached to a special area of activity. The advantages and the problems were evaluated according to GENAB: s overall objective. Since the report is delimited to only evaluate the economic benefit and not those economic costs that the measurement brings, it is still unclear which type of measurement that is economically viable for GENAB. What can be established is that metering in distribution substations gives possibilities to gain a more oriented picture of how the power distributes in the net. Metering in distribution substations results in both net- and customer advantages for GENAB. The measurements give GENAB better conditions to meet authority requirement in terms of power quality. With measurements, transformers and cables can be used more efficiently, which gives an improved power and energy balance. It also gives a better control over energy losses. Measurements contribute to an improved operation monitoring and also an improved customer service by giving information about discrepancies in the power network to those who are interested. General problems in form of disorder functions, rounding problems, program problems et cetera can appear but despite of that, the advantages outweigh the problems and the costs. This report has become the basis for a future pilot project that will be started at GENAB.
Keywords: Elkraftteknik; Electric power engineering